Construction of two photoluminescent sulfur-containing cadmium(II) coordination polymers with 4-connected topology based on a methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate ligand. (4th March 2018) - Xue, Li-Ping; He, Sheng-Jun; Wang, Xiao-Ning; Zhang, Dan-Dan
ABSTRACT: Two new Sulfur-containing Cadmium(II) coordination polymers [Cd(HL)2 ](2H2 O) n (1 ) and [Cd(L)(bmie)(H2 O)](H2 O) n (2 ) (H2 L = methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate, and bmie = 1, 2-bis(imidazol-1′-yl)ethane) have been successfully constructed and structurally characterized by the single-crystal X-ray diffraction and other characterization techniques, such as elemental analysis, IR spectroscopy and thermogravimetric analysis. Structural analyses reveal that complex1 exhibits a hydrogen bonded-extended 3D supramolecular structure based upon 4-connected sql layers assembled from single Cd(II) centers as nodes. Complex2 features a 3D network which can be rationalized as a rare 4-connected cdl topology. It is shown that the H2 L ligand is a suitable building block in constructing coordination polymers with structural diversities. Moreover, solid photoluminescent properties have been investigated. GRAPHICAL ABSTRACT: